Multibeam bathymetry raw data (EM 120 echosounder entire dataset) of RV MARIA S. MERIAN during cruise MSM19/1c - Wenau, Stefan; Zabel, Matthias (PANGAEA, 2025)
Raw bathymetry data were collected using the ship's own Kongsberg EM120 multibeam echosounder during the RV MARIA S. MERIAN cruise MSM19/1c. The cruise took place between 2011-10-12 and 2011-10-21 (Walvis Bay, Namibia – Walvis Bay, Namibia), as training and capacity building course in the frame of the BMBF FONA / SPACES program. Bathymetry data were collected on the Namibian shelf and upper continental slope, along with seismics and sub-bottom (Parasound) profiling. No sound velocity profiles (SVP) were collected during the cruise. Data are unprocessed and contain incorrect depth measurements (artifacts). Data can be processed e.g. with the open source software package MB-System (Caress, D. W., and D. N. Chayes, MB-System: Mapping the Seafloor, http://www.mbari.org/products/research-software/mb-system/, 2022).
Keywords: Bathymetry; Multibeam Echosounder